The Effect of Economic Opportunity and Family Background on Adolescent Cohabitation on Adolescent Cohabitation and Childbearing among Low-Income Blacks - Olsen, Randall J.; Farkas, George (Journal of Labor Economics, 1990)
This article uses a hazards model permitting continuous covariates and fixed effects to estimate the effect of local employment opportunity and family background on the cohabitation and childbearing of black youths from low-income households. Support is found for W. J. Wilson's hypothesis that employment opportunity encourages the formation of cohabitational unions, as well as for the "opportunity-cost" hypothesis that employment opportunity discourages childbearing outside such unions. However, the latter effect appears to be larger, suggesting that the opportunity-cost hypothesis is the primary channel through which higher employment rates result in lower rates of illegitimacy among underclass youths.